Problem Solving Ability Through E- Learning With Pbl of Ethnomathematics Reviewed From Student Character In Primary School - Febrinasti, Rina; Rochmad, Rochmad; Isnarto, Isnarto (Journal of Primary Education, 2021)
The objectives of this study were to 1) determine the effectiveness of the PBL-ethnomatematics online learning model in improving students' mathematical problem-solving abilities, 2) to describe the mathematical problem-solving abilities of students using PBL-ethnomatics online learning reviewed from the student character. The research method used in this study was a mixed method with a sequential explanatory design. The data collection technique was done by using problem solving ability tests, observation, interviews, questionnaires and documentation. The quantitative research was analyzed by using the t test. The results showed that (a) the average of mathematical problem solving ability in the class with PBL-ethnomatics online learning was more than the a minimum completeness criteria of 68, (b) the mathematics problem solving ability of sudents with PBL-ethnomatematics online learning had reached 75% classical completeness, (c) the average ability of mathematical problems solving with PBL-ethnomathematics online learning is better than the average ability of mathematical problems solving with PBL online learning. Based on the analysis of mathematical problem-solving abilities reviewed from student character, the following results were obtained: concluded that students who have a disciplined character are better at solving problems than students who have a character of environmental care.